Collective Bargaining in the Public Services of Canada - Anderson, John c.; Kochan, Thomas A. (Relations industrielles / Industrial Relations, 1977)
This paper examines the existing System of collective bargaining in the Public Service of Canada and the legislative suggestions of the Parliamentary Committee on Employer-employee Relations in the Public Service in light of the results of two major empirical investigations of collective bargaining in the federal public service of Canada.